2002
DOI: 10.1210/jcem.87.2.8182
|View full text |Cite
|
Sign up to set email alerts
|

Serum TSH, T4, and Thyroid Antibodies in the United States Population (1988 to 1994): National Health and Nutrition Examination Survey (NHANES III)

Abstract: NHANES III measured serum TSH, total serum T(4), antithyroperoxidase (TPOAb), and antithyroglobulin (TgAb) antibodies from a sample of 17,353 people aged > or =12 yr representing the geographic and ethnic distribution of the U.S. population. These data provide a reference for other studies of these analytes in the U.S. For the 16,533 people who did not report thyroid disease, goiter, or taking thyroid medications (disease-free population), we determined mean concentrations of TSH, T(4), TgAb, and TPOAb. A refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

53
725
20
33

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,062 publications
(831 citation statements)
references
References 32 publications
53
725
20
33
Order By: Relevance
“…These percentages are comparable with those reported in some other studies [9,13,15,22], yet are higher than those reported by others [8,23,24]. Estimates of subclinical hypothyroidism prevalence vary by the type of population accessed, i.e., sampled from community, hospital, nursing home or primary care, concurrent comorbidity and the TSH assay, and cut-off values used [25]. …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These percentages are comparable with those reported in some other studies [9,13,15,22], yet are higher than those reported by others [8,23,24]. Estimates of subclinical hypothyroidism prevalence vary by the type of population accessed, i.e., sampled from community, hospital, nursing home or primary care, concurrent comorbidity and the TSH assay, and cut-off values used [25]. …”
Section: Discussionsupporting
confidence: 84%
“…The prevalence in women over age 80 years is lower, about 6% [25]. In our study, 15.4% of those 60 years and above had subclinical hypothyroidism, while only 9.9% of <60 years age had high TSH, and this was not statistically significant; however, mean TSH was significantly higher in elderly.…”
Section: Discussioncontrasting
confidence: 61%
“…When patients were classified as affected by benign thyroid disease or PTC according to the results of cytology, the age-dependent reduction of TSH levels was highly significant in the first group, while in patients with PTC this phenomenon was much less evident. Indeed, the TSH levels in patients with PTC were close to the agespecific distribution of TSH found in people living in iodine sufficient areas, as reported in the NHANES III survey (Hollowell et al 2002, Aoki et al 2007, Surks & Hollowell 2007. These data strongly suggest that in our series of patients, the higher levels of TSH in PTC with respect to BTND are not due to an increase of thyrotropin in patients with thyroid cancer, but are mainly related to the reduction of serum TSH in patients with nodular goiter.…”
Section: E Fiore Et Al: Tsh and Risk Of Ptcsupporting
confidence: 88%
“…We have no solid explanation for this inconsistency. Nevertheless, because women tend to have a higher TSH [32], one may anticipate women would be more susceptible to DTC if they are not over-represented in the subgroup undergoing surgery for benign conditions than men.…”
Section: Discussionmentioning
confidence: 99%